1998
DOI: 10.1038/bjc.1998.396
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of patients' mental adjustment to cancer: patient characteristics and social support

Abstract: Because being diagnosed with cancer is considered to be extremely stressful, cancer patients' mental adjustment has been widely studied. Previous studies have revealed that cancer patients' mental adjustment is correlated with the quality of life and the degree of psychological distress and have suggested that one of the most adaptive adjustments is 'fighting spirit' whereas one of the most maladaptive is 'helplessness/hopelessness'. However, little is known about the association between patients' mental adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 34 publications
4
64
0
1
Order By: Relevance
“…Older men have been reported as more likely to feel 'helpless and hopeless' than younger men (Akechi et al, 1998), and may therefore need more emotional support. Older men are likely to be aware of prostate cancer (MORI, 1999), although few feel that sufficient information has been directed specifically to them (Health Education Authority, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Older men have been reported as more likely to feel 'helpless and hopeless' than younger men (Akechi et al, 1998), and may therefore need more emotional support. Older men are likely to be aware of prostate cancer (MORI, 1999), although few feel that sufficient information has been directed specifically to them (Health Education Authority, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Because our previous study indicated that the physical function of cancer patients was associated significantly with hopelessness/helplessness, 28 and several studies demonstrated a significant association between hopelessness and suicidal ideation, 13,17 patients' hopelessness might serve as a mediator between physical function and suicidal ideation. Conversely, although a significant association was indicated by the univariate analysis, the multivariate analyses did not show any such significance.…”
Section: Physical Function and Suicidal Ideationmentioning
confidence: 90%
“…This information was obtained in a structured interview 28 conducted at the baseline and follow-up examinations. In the interview, the patients were asked whether they had confided in someone since being diagnosed with cancer and, if so, in whom.…”
Section: Social Supportmentioning
confidence: 99%
“…Cancer is one of several illnesses that increase the risk of suicide in Asian countries (22)(23)(24)(25)(26)(27)(28). In Korea, cancer has been named as a suicide risk factor when coupled with comorbidities such as psychiatric diseases (22).…”
Section: Introductionmentioning
confidence: 99%